FUZZY LOGIC CONTROL OF A HEXAPOD ROBOT WITH BOUNDING GAIT - Soyguder, Servet; Alli, Hasan (World Scientific Publ Co Pte Ltd, 2010)
In this study, dynamic model, simulation and control of a six-legged hexapod robot have been performed for a bounding gait. To obtain the numerical simulation of the system with bounding gait, the different dynamic structures have been solved in a sequential closed loop (stance, flight phase). Spring Loaded Inverted Pendulum (SLIP) has been used as a dynamic model to simplify the simulation of the system and ease to understand the bounding gait. In addition, the hexapod robot with bounding gait has been controlled by Fuzzy Logic Control algorithm. The number of the performed control action during the phases of bounding gait in this study is smaller than those of the studies in the literature. Consequently, the proposed improvements in this study make both the system control easy and the system performance increase by decreasing the run time for each loop.
13th International Conference on Climbing and Walking Robots and the Support Technologies for Mobile Machines -- AUG 31-SEP 03, 2010 -- Nagoya Inst Technol, Nagoya, JAPAN